1989
DOI: 10.1046/j.1537-2995.1989.29589284144.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of granulocyte‐releasing products and chemiluminescence during cytapheresis

Abstract: During the procedures of centrifugation leukapheresis and plateletpheresis, donors occasionally experience adverse clinical reactions. The possibility of whether the activation of granulocytes and the subsequent release reactions, which may have been triggered by this extracorporeal circuit, were responsible for these adverse effects was evaluated. Six blood samples were obtained at set intervals during cytapheresis. Of these samples, four were taken directly from the donor. The remaining two were drawn from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2000
2000
2000
2000

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Neutrophil activation during apheresis is poorly investigated. Lindena et al 5 found no increase in the production of oxygen radicals during apheresis; the release of granulocyte degranulation products (elastase and β‐glucuronidase) increased, but they concluded that there were no clinical effects in the donor. In accordance with that study, Jungi and coworkers 6 found no functional differences in neutrophil activity after plasmapheresis.…”
mentioning
confidence: 99%
“…Neutrophil activation during apheresis is poorly investigated. Lindena et al 5 found no increase in the production of oxygen radicals during apheresis; the release of granulocyte degranulation products (elastase and β‐glucuronidase) increased, but they concluded that there were no clinical effects in the donor. In accordance with that study, Jungi and coworkers 6 found no functional differences in neutrophil activity after plasmapheresis.…”
mentioning
confidence: 99%